2010
DOI: 10.3136/fstr.16.523
|View full text |Cite
|
Sign up to set email alerts
|

Different Distributions of .ALPHA.-Glucosidases and Amylases in Milling Fractions of Rice Grains

Abstract: The distribution of starch-degrading enzymes in dormant rice grains was investigated with specific antibodies against α-glucosidases, α-amylases, and β-amylases. The α-glucosidases were predominantly localized in the inner endosperm. The α-amylases were mainly localized in the outer layers, and the β-amylases were distributed in whole grains. We propose a model to demonstrate how these enzymes degrade starch during rice cooking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…We here discuss the results for these two cultivars in comparison with the previous results for Koshihikari. To describe Koshihikari, we quoted part of the results of the distribution and enzyme behavior in Koshihikari from previous reports (Tsuyukubo et al, 2010;Tsuyukubo et al, 2012) (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We here discuss the results for these two cultivars in comparison with the previous results for Koshihikari. To describe Koshihikari, we quoted part of the results of the distribution and enzyme behavior in Koshihikari from previous reports (Tsuyukubo et al, 2010;Tsuyukubo et al, 2012) (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we revealed the distribution of starch-degrading enzymes in rice grains and their elution behavior during cooking with a specific antibody against each enzyme, including α-glucosidase, α-amylases, β-amylase, pullulanase and isoamylase, in Koshihikari cultivars (Tsuyukubo et al, 2010;Tsuyukubo et al, 2012). We also showed that starch hydrolytic activities and reducing sugar production differ with cooking temperature among Koshihikari, Nipponbare, Habutaemochi, Yumetoiro and Milkyqueen cultivars .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was shown that RNAi-mediated suppression of α-amylase genes in ripening seeds resulted in fewer chalky grains under high-temperature conditions, and the extent of the decrease in the ratio of chalky grains was highly correlated to decreases in the expression of Amy1A, Amy1C, Amy3A and Amy3B. 32) Furthermore, Tsuyukubo et al (2010Tsuyukubo et al ( , 2012 36,37) have demonstrated that AmyI-1 (Amy1A) and AmyII-4 (Amy3D) proteins existed in the outer layers (100 to 80% fractions) of rice grain (cv. Koshihikari), while α-glucosidase and AmyII-3 (Amy3E) were mainly detected in the inner layers (80 to 0% fractions) by immunoblotting with the specific antibodies.…”
Section: Breaking Test Of Cooked Rice Of Perfect and Chalky Grainsmentioning
confidence: 99%
“…Isoamylases can debranch glycogen, but rarely attack pullulan, while the pullulanase shows a reverse specificity. Several studies revealed that starch-debranching enzymes not only hydrolyze amylopectin in storage starch during germination, but also play essential roles in amylopectin biosynthesis (Ball et al, 1996;Kubo et al, 1999).In a previous study, we revealed the distribution of enzymes in dormant grains by employing a specific antibody against each enzyme, such as α-glucosidase (against an ONG2 specific peptide), α-amylase, and β-amylase (Tsuyukubo et al, 2010) antibodies. Having clarified the activity profiles of enzymes in rice grains (Mabashi et al, 2009), we encountered difficulty in measuring enzyme activity in cooking water, possibly due to a low abundance of enzymes.…”
mentioning
confidence: 99%